MULTIPLE INTELLIGENCE THEORY FOR EFL DISADVANTAGED STUDENTS OF NON–FEE PAYMENT SCHOOL - cut raudhtaul miski (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
After more than thirty five years, multiple intelligence theory of Howard Gardner is still used to help teaching and learning process in the classroom. Teachers can guide students to maximize their English language learning by optimizing their potential intelligences. Though so, discussion on multiple intelligence toward disadvantaged students is not adequate enough. This paper will figure out the usefulness of the Multiple intelligence theory to facilitate the disadvantaged students in learning English language in the classroom especially who learn at non - fee paying school. Hopefully that this paper benefits for teachers who teach disadvantaged students, those who are working to improve the quality of education for disadvantaged students, and give a useful light to student teacher’s knowledge about the unique circumstances of disadvantaged students.